Global aHUS Registry Analysis of Patients Switching to Ravulizumab From Eculizumab - Franz Schaefer; Imad Al-Dakkak; Katerina Anokhina; David Cohen; Larry A. Greenbaum; Gema Ariceta (Kidney International Reports)
Introduction: Atypical hemolytic uremic syndrome (aHUS) is a progressive rare disease that, if untreated, can result in severe organ damage and death. Ravulizumab, a next-generation terminal complement inhibitor, provides immediate, complete, and sustained complement C5 inhibition. Real-world data in patients with aHUS who switched to ravulizumab from eculizumab are lacking. Methods: The Global aHUS Registry is a multicenter study (NCT01522183) collecting data on adult or pediatric patients with an aHUS diagnosis, regardless of treatment. Patient characteristics, genetic data, hematological and renal parameters, clinical events (e.g., dialysis and kidney transplantation), and adverse events (AEs) were extracted from patients who switched to ravulizumab from eculizumab up to July 3, 2023. Results: Overall, 60 patients switched to ravulizumab (adult: n = 43; pediatric: n = 17); 11 patients were excluded from effectiveness and genetic analyses (N = 49; adult: n = 40; pediatric: n = 9) because they received <3 months ravulizumab treatment and/or had >1 month between eculizumab discontinuation and ravulizumab initiation. Pathogenic complement variants were identified in 11 of 49 patients (22%); the most common was a complement factor H variant (n = 5/49 [10%]). During ravulizumab treatment, 20 AEs occurred in 13 patients, with no unexpected AEs and only 3 treatment-related AEs (infusion reaction, headaches, and fatigue). No meningococcal infections or deaths were reported. No new events of dialysis, kidney transplantation, or thrombotic microangiopathy were reported. Renal and hematological parameters remained stable after switching to ravulizumab. Conclusion: This is the first real-world cohort analysis of data from patients treated with ravulizumab and reinforces the real-world safety and effectiveness data of ravulizumab in patients with aHUS who switched from eculizumab.